An enriched sugarcane diversity panel for utilization in genetic improvement of sugarcane - Nathanael D. Fickett (Nature Portfolio, 2020)
Abstract Sugarcane crop is important for both sugar and biofuels. A world collection of sugarcane and related grasses (WCSRG) maintained at Miami, FL contains > 1,200 non-redundant clones of different species and genera within the Saccharum complex. However, linkage of undesirable alleles with useful genes in wild species has hindered its efficient utilization in sugarcane breeding. A core collection developed previously with smaller number of clones representing WCSRG did not take into account > 120 wild/exotic clones maintained at the USDA-ARS Sugarcane Research Unit in Houma, Louisiana. Moreover, the genome complexity and sub-tropical to temperate growing climate of Louisiana warrant a region-specific core collection that can be used for base-broadening breeding aimed at efficient introgression of desirable alleles. Genetic diversity of 1,485 clones within WCSRG and Louisiana (commercials, wild/exotic) using 423 SSR alleles showed an average gene diversity (h) at 0.208 among all species groups where Erianthus-like Saccharum species (ELSS), Miscanthus spp., and S. spontaneum each formed a distinct cluster, Saccharum robustum, S. officinarum, hybrid cultivars, and S. edule grouped together in a major cluster, and Saccharum sinense and S. barberi formed distinct grouping. A 309-clone diversity panel (SDP1) was developed that captured the genetic diversity based on the combination of maximum length subtree and manual selection to maximize representation of Louisiana clones and minimize import of clones from Miami. SDP1 shared 324 alleles out of the 423 alleles in the entire population of 1,485 clones and captured the genetic diversity of the entire collection with an average gene diversity (h) at 0.163. The variation within (11–17%) and among (83–89%) the populations in SDP1 were comparable with the entire population of 1,485 clones (9–15% and 85–91%, respectively). The breadth of the genetic variation of SDP1 was exemplified by the intra- and inter-specific diversity of a 190-clone mini-core collection with markers derived from known cold-responsive genes. SDP1 will facilitate genome-wide association studies for identification of trait-specific markers for use in marker-assisted breeding in Louisiana and elsewhere.